2022
DOI: 10.1021/acs.energyfuels.1c04082
|View full text |Cite
|
Sign up to set email alerts
|

IrO2-Modified RuO2 Nanowires/Nitrogen-Doped Carbon Composite for Effective Overall Water Splitting in All pH

Abstract: Development of active catalysts for the electrochemical hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) are of prime importance for the commercialization of the proton-exchange membrane (PEM)/ anion-exchange membrane (AEM) water electrolyzer. Here, we report synthesis of an IrO 2 -modified RuO 2 nanowires/nitrogendoped carbon composite for overall water splitting at all pH. This catalyst exhibits excellent OER activity in 0.5 M H 2 SO 4 solution with a low overpotential of 188 mV at 10 mA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 72 publications
1
22
0
Order By: Relevance
“…Researchers have focused on storing these renewable energies and utilizing them during lack of energy. Electrolyzers and fuel cells are gaining attention nowadays for this purpose. In an electrolyzer, hydrogen evolved at the cathode (hydrogen evolution reaction or HER), which can be stored as a fuel, and oxygen evolved at the anode (oxygen evolution reaction or OER) from water. In a fuel cell, hydrogen is used as the fuel in the anode (hydrogen oxidation reaction or HOR) to produce electricity, and oxygen or air is used at the cathode (oxygen reduction reaction or ORR). There are two main commercially available methods for water electrolysis as well as fuel cells such as an anion exchange membrane (AEM) and a proton exchange membrane (PEM) . PEM-based devices have more advantages than AEM-based devices as they have high power density and comparatively more durability. , Although there are several advantages of PEM-based devices, AEM-based devices are gaining more attention as there are several cheaper and easily available lower-transition-metal-based electrocatalysts for OER and ORR in an AEM environment. , However, these catalysts show very poor stability in a PEM environment.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have focused on storing these renewable energies and utilizing them during lack of energy. Electrolyzers and fuel cells are gaining attention nowadays for this purpose. In an electrolyzer, hydrogen evolved at the cathode (hydrogen evolution reaction or HER), which can be stored as a fuel, and oxygen evolved at the anode (oxygen evolution reaction or OER) from water. In a fuel cell, hydrogen is used as the fuel in the anode (hydrogen oxidation reaction or HOR) to produce electricity, and oxygen or air is used at the cathode (oxygen reduction reaction or ORR). There are two main commercially available methods for water electrolysis as well as fuel cells such as an anion exchange membrane (AEM) and a proton exchange membrane (PEM) . PEM-based devices have more advantages than AEM-based devices as they have high power density and comparatively more durability. , Although there are several advantages of PEM-based devices, AEM-based devices are gaining more attention as there are several cheaper and easily available lower-transition-metal-based electrocatalysts for OER and ORR in an AEM environment. , However, these catalysts show very poor stability in a PEM environment.…”
Section: Introductionmentioning
confidence: 99%
“…The 2D sheetlike structure of the CoO x /CN x catalyst was confirmed by the FE-SEM and TEM images (Figure b,c). Strong synergistic interactions between the components may be a reason for the high activity of the catalyst. Several groups , reported that the synergistic interaction of different components, which can modify the morphology of the components to expose more active sites or adjust the intrinsic electronic properties through molecular/atomic orbital coupling. Through tuning the electronic structures of the dopants and host metal atoms, the synergistic interaction also influences charge transfer kinetics, thereby reducing the kinetic energy barriers in catalysis .…”
Section: Resultsmentioning
confidence: 99%
“…Water splitting contains two half reactions, oxygen evolution reaction (OER) and hydrogen evolution reaction (HER), which take place at the anode and cathode, respectively. , The HER involves a two-electron transfer process, but unlike HER, OER goes through a four-electron transfer process . This requires extra energy to break the O–H bond and finally form the O–O bond.…”
Section: Introductionmentioning
confidence: 99%